Análise clínica e microbiológica de úlceras venosas de pacientes atendidos em Unidades Básicas de Saúde de Goiânia - SANTOS, Silvana de Lima Vieira dos (2012)
This cross-sectional study was performed in the dressing rooms of the primary healthcare network of Goiânia, Goiás, Brasil, with the following objectives: to identify the prevalence of Gram-negative bacteria (GNB) in venous ulcers (VU) with clinical signs of infection; analyze the susceptibility profile of the isolates; detect the production of AmpC β-lactamases and metallo-beta-lactamases, and extended spectrum beta-lactamase (ESBL); describe the clinical signs and symptoms of infection in VU; evaluate the wounds clinical stage of infection and its relationship with the presence of GNB. The data were analyzed by means of descriptive statistics procedures, proportion and Chi-square tests (p<0.05). All ethical aspects were followed. The participants were 69 patients with venous ulcers, with or without arterial complication, totaling 98 wounds. It was verified that 74.5% of the wounds showed GNB growth, particularly enterobacteria (53.8%) and non-fermenting gram-negative bacteria (46.2%). The prevalent species among the enterobacteria was Escherichia coli (24.5%), followed by Enterobacter aerogenes, Pantoea agglomerans and Proteus mirabilis (12.2% each). Regarding the non-fermenting gram-negative bacteria, the prevalent genre was Pseudomonas (66.6%), particularly the species P. aeruginosa (59.5%), present in 25.5% of the analyzed wounds. Regarding the susceptibility profile of the enterobacteria, the highest resistance rates were to tetracycline (38.8%) and amoxicillin-clavulanic acid (26.5%). Among P. aeruginosa, the highest resistance was observed for cefoxitin (100%). Regarding the production of the AmpC enzyme, 30% of the microorganisms in the CESP (Citrobacter spp., Enterobacter spp., Serratia spp. and Providencia spp.) group, and 100% of the P. aeruginosa were resistant to cefoxitin. The remaining microorganisms of the CESP group (70%) that were sensitive to cefoxitin were subjected to a confirmatory test, and 37.5% were found to be positive for the production of the AmpC enzyme. Regarding metallo-beta-lactamase, 23.8% of the non-fermenting gram-negative bacteria showed reduced sensitivity to imipenem, meropenem or ceftazidime. When subjected to the confirmatory test, 8% of the P. aeruginosa were positive for the MBL enzyme. Regarding the clinical signs and symptoms of infection, the highlighted results with >70% frequency are: opaque and/or reddish brown discoloration; increase in exudate volume and pain. Stage-three infection was the most prevalent (71.4%). An association was found between cellulitis and friable granulation tissue that bleeds easily and the culture for GNB. In conclusion, the presence of gram-negative pathogens with resistance profiles in primary healthcare patients suggests the need to implement microbiological surveillance for patients with VU experiencing a prolonged or difficult healing process, and that the identification VU infection should be guided by knowledge regarding the etiology, classic characteristic and clinical stages of infection.